Optimization of Cutting Parameters, Condition and Geometry in Turning AISI 316L Stainless Steel Using the Grey-Based Taguchi Method - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2017)
In this study, experimental optimization of cutting forces, surface roughness and the hardness of material after turning of AISI 316L stainless steel, using conventional and wiper insert cutting tools under dry, CO 2 and MQL cutting conditions, is presented. The influences of feed rate, cutting depth, and cooling system on surface roughness, cutting force and material hardness were examined. In order to optimize the turning process, Grey relational analysis optimization method was used. The optimal machinability parameters of AISI 316L stainless steel with coated carbide insert were successfully determined.
Keywords: MINIMAL QUANTITY LUBRICATION; SURFACE-ROUGHNESS; TOOL WEAR; COOLANT; CHIP; TEMPERATURE; PERFORMANCE; MQL